MENEGUHKAN KEMBALI KEBERAGAMAN INDONESIA - Sudarto S. (Masyarakat Indonesia, 2017)
The basic feature of democracy is diversity. So the main issue in democracy is how to manage the diversity according to the principles of equality and justice. In this regard, it is undeniable that Indonesia is a plural country with the largest Muslim population in the world. On the one hand Indonesia is in the maturation of democracy, but on the other hand Indonesia is still faced with many challenges in managing the diversity. The plurality of problems as described above is caused by the following: First, there are still many regulations produced by the state which in essence precisely complicate the management of the diversity itself. Included in this problem is the lack of protection of freedom of religion and belief by law enforcement officials. Second, the strong desire to dominate from dominant groups to smaller groups of quantities. Third, felt still fragile foundation of tolerance in society body itself. The three roots of the problem have an intercausal relationship. As a result, non-mainstream groups become victims of discrimination, especially local religious groups, which occur in a structured, widespread and systematic manner. The problem is how to rearrange the Indonesian religion according to the principles of equality and justice especially to the local religious groups of the archipelago? To answer the big question, the author uses civic pluralism approach offered by Robert W Hefner. According to Hefner, society can be called a civic pluralist, when each member throws away efforts to suppress and reduce diversity (Hefner, 2003: 195). This paper aims to offer the concept of diversity management that is expected to contribute to re-establish Indonesia's diversity.Keywords: local religions, regulation, management of diversity, restructurization, and religionization ABSTRAKFitur permanen demokrasi adalah keberagaman. Persoalan pokok dalam negara demokrasi adalah bagaimana mengelola keberagaman tersebut dalam prinsip kesetaraan dan berkeadilan. Dalam kaitan ini tidak bisa dipungkiri, Indonesia adalah negara majemuk dengan penduduk muslim terbesar di dunia. Pada satu sisi Indonesia sedang dalam pematangan demokrasi, namun di pihak lain Indonesia masih dihadapkan dengan banyak tantangan dalam mengelola keberagaman dimaksud. Problem-problem kemajemukan di Indonesia sebagaimana terurai di atas disebabkan oleh antara lain: Pertama masih banyaknya regulasi yang diproduksi oleh negara yang pada esensinya justru menyulitkan pengelolaan keberagaman itu sendiri. Kedua, kurangnya tindakan perlindungan kebebasan beragama dan berkepercayaan bagi masyarakat oleh aparat penegak hukum. Ketiga, dirasakan masih rapuhnya pondasi toleransi di dalam tubuh masyarakat itu sendiri. Ketiga akar masalah tersebut memiliki hubungan interkausal. Akibatnya kelompok-kelompok non mainstream yang menjadi komponen kemajemukan terutama dari kalangan non-mainstream menjadi korban diskriminasi, terutama komunitas agama lokal nusantara yang terjadi secara terstruktur, sistematis dan massif. Persoalannya bagaimana mengelola kembali keberagaman Indonesia menurut prinsip kesetaraan dan berkeadilan bagi setiap warga negara, utamanya bagi komunitas agama lokal nusantara? Untuk menjawab pertanyaan besar tersebut penulis akan menggunakan pendekatan “Civic pluralism” yang digunakan oleh Robert Hefner. Menurut Hefner, masyarakat dapat disebut civic pluralist, ketika anggota-anggotanya membuat jauh-jauh upaya atau niat untuk menekan atau mengurangi keberagaman (Hefner, 2003:159). Tulisan ini bertujuan untuk menawarkan konsep pengelolaan keberagaman yang diharapkan dapat berkonstribusi mengukuhkan kembali keberagaman Indonesia.Kata kunci: agama lokal, agamaisasi, regulasi, pengelolaan keberagaman, restrukt